Associação entre atividade física e hipertensão arterial em adultos brasileiros: uma revisão da literatura - Mussi, Ricardo Franklin de Freitas (2012)
Through the speed which knowledge is produced and available in many different banks of data storage, it’s understood the needing of addressing on these publications, in order to intend to approach of what is relevant, indispensable or superfluous in the academic-scientific community, since scientific divulgation in health field is growing in an unprecedented way. Aware of this scenario, this literature review intended to describe the profiles of the scientific production which associate "Physical Activity" and "Arterial Hypertension" in groups of Brazilian adults present in the collection of Brazilian journals from SciELO, specifically under the desire of identifying the epidemiological design used, check the sample characteristics, check chosen variables, and describe the occurrence of the investigated association. Methodologically, all article found were pre-selected from Boolean search containing simultaneously the descriptors Physical Activity (or Physical Exercise or Exercise) and Arterial Hypertension (or Hypertension and Systemic Arterial Hypertension), 56 different items were found, after refining 19 Articles were accepted to join this review. We identified the quantitative balance between cross-sectional studies and intervention studies (most without intervention randomization). The population profiles are eminently urban, citing little about race / color and reflecting about demographic variables. The large number and diversity of variables and techniques for their obtainment becomes difficult relationship or comparison of results. We detected the presence of sedentary in the cross-sectional studies, especially among poor people, women, and low educated people. Similarly it was found a high prevalence of hypertension among men. What concerns about the association between Physical Activity and Hypertension, it was identified strong evidence of inverse association. In intervention studies we found recurrent Post-exercise Hypotension. In cross-sectional studies, with probabilistic samples, the association was not fully confirmed, with studies that found statistically significant association, by using collection by telephone survey, and in other studies, it was only observed this association after stratification. Thus, this work offer indicative of needing for new researches that intend to investigate issues about multiple modalities and intensities of Physical Exercise, and the varied dimensions of Physical Activity that best associate with ideal pressure levels, with larger and more diverse sample groups, especially allowing the insertion of rural communities and black race / color people.